แนวทางพัฒนาการประเมินผลการปฏิบัติงานของครู โรงเรียนบ้านบางกะปิ - กุลสุวรรณ ปิ่นประภาภรณ์; เจริญกุล นันทรัตน์ (An Online Journal of Education, 2018)
The purposes of this research were to: 1) Study the present conditions and desirable condition of teacher performance evaluation. 2) Develop the approaches for teachers’ performance evaluation of Ban-bangkapi School By using Mixed methods research. Population used in this study was Ban-bangkapi School. The respondents were composed of 4 administrators and 98 teachers from 132 populations. The instruments used in the study were questionnaires, interviews, and suitability and feasibility. The quantitative data were analyzed using frequency, percentage, mean, s.d. and PNI modified, while the qualitative data were analyzed by content analysis. The research results revealed that The status of Teacher performance evaluation in Ban-Bangkapi school was high and desirable condition was the highest. The top three of essential needs were 1) Giving feedback (PNImodified = 0.31) 2) Purpose of performance evaluation (PNImodified = 0.30) 3) Tool for performance evaluation (PNImodified = 0.28) Approach for developing teacher performance evaluation of Ban-Bangkapi School by implement the quality management process according to the Deming cycle (PDCA) had 4 steps were Step 1) Planning was the preparation process, to raise the awareness and emphasize the performance evaluation. Step 2) Do, administrators and teachers coordinate to plan the content and material for performance evaluation and also had workshop about teacher’s performance evaluation. Step 3) Check administrators and boards coordinate to investigate, collect, analysis data of performance evaluation and giving feedback Step 4) Act, administrators used the result to support the suggestion for the teacher’s to improve their performance and to create the development plan.